Characteristics of fricatives consonants orthography in Brazilian children - Paschoal, Larissa [UNESP]; Pezarini, Isabela de Oliveira [UNESP]; Vaz, Suellen [UNESP]; Chacon, Lourenço [UNESP] (Academia Brasileira de Audiologia, 2014)
Purpose (1) describe children’s orthographic performance in the record of fricative consonants in a position of simple syllabic attack; (2) verify the influence of the accent in errors occurrence; and (3) categorize the kind of errors found. Methods Fifteen children’s text productions were selected, they attended the First grade of Primary School in 2001, referred to 14 thematic proposals. From these productions, all the words with occurrence of fricative consonants in syllabic position of simple attack were selected. These occurrences were distributed in hits and errors, these were, then, organized according to the appearance in pre-tonic, tonic and post-tonic syllables, unstressed monosyllables and tonic monosyllables. Results It was noted that (1) a predominance of hits compared to the errors; (2) the non-relevance of the accent in the record of unconventional fricatives; (3) higher occurrence of phonological substitutions, followed by the orthographical ones and, finally, in lower number, omissions; (40 predominance of errors inside the fricative phonological class. Conclusion The group of children studied, even in the beginning of literacy, already shows very stable in the record of graphemes that is sent to the fricative phonemes. At last, it was observed that the errors seems to be motivated, mainly, by the difficulty of these children with the spelling of PB.

Objetivos (1) descrever o desempenho ortográfico de crianças no registro das consoantes fricativas em posição de ataque silábico simples; (2) verificar a influência do acento na ocorrência de erros; (3) categorizar a tipologia dos erros encontrados. Métodos Foram selecionadas produções textuais de 15 crianças, que cursaram a 1ª série do Ensino Fundamental no ano de 2001, referentes a 14 propostas temáticas. Dessas produções, foram selecionadas todas as palavras com ocorrência de consoantes fricativas em posição silábica de ataque simples. Essas ocorrências foram distribuídas em acertos e erros, organizados conforme aparecessem em sílabas pretônicas, tônicas, postônicas, monossílabos átonos e monossílabos tônicos. Resultados Observou-se (1) predomínio de acertos em relação a erros; (2) não relevância do acento no registro não convencional das fricativas; (3) maior ocorrência de substituições fonológicas, seguidas de ortográficas e, em menor número, omissões; (4) predomínio de erros dentro da classe fonológica das fricativas. Conclusão O grupo de crianças estudado, ainda que em início de alfabetização, já se mostra bastante estável no registro dos grafemas que remetem aos fonemas fricativos. Observou-se que o erro parece ser motivado, principalmente, pela dificuldade dessas crianças com as convenções ortográficas do Português Brasileiro.
Características da ortografia de consoantes fricativas na escrita infantil
Keywords: Escrita manual; Desenvolvimento da linguagem; Criança; Fonética; Linguística; Handwriting; Language development; Child; Phonetics; Linguistics